Designing play: Young children's play and communication practices in relation to designers' intentions for their toy. Issue 1 (March 2018) - Yamada-Rice, Dylan
This article looks at the way in which changes in technology, as well as wider social and cultural patterns, bring about new materials in the landscape of young children's communication practices and play. This is done in relation to a new form of screen-less digital toy known as Avakai. Avakai are a set of digitally interactive wooden dolls that combine set movements and sounds. The study had two parts that focused first on the toy's design and second on how it was used in combined play and communication practices by seven 4- to 6-year-olds. This was to ascertain the extent to which the design and children's use aligned. Data were gathered through conversations and email exchanges with the toy designers and observations of the children's play and communication practices with the toy. All data were transcribed and analysed using thematic analysis. Three key findings are discussed in relation to the alignment of these two areas: (1) children's customisation of the toy design, (2) designing to produce emotional narratives in play and (3) the use of a compartment in the toy's base. Each finding is described in relation to the designers' backgrounds and intentions for the toy, and then the children's use in terms of play and communication. In doing so, the extent to which the child and the toy's design influenced play and communication practices is shown. These findings make a contribution to the field of materialities in young children's communication practices when playing. This is ever important given the evolving speed of new materials and technologies for play and communication. In particular to how non-visual modes of communication are foregrounded in the absence of screens. In addition, it adds to prior research that has taken an object ethnographic approach by uniquely considering the toy in relation to primary data about the toy designers' backgrounds and design decisions rather than from what can be inferred from the object.